Strengthening Research Management In The International Collaboration - Wahyono, Sri; Asropi, Asropi; Silitonga, Mala Sondang (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2024)
The number of scientific publications produced by Indonesian Collaborating Partners is still not optimal. When comparing the number of international research partnerships with the indicator of the number of Research Permits issued, the overall performance of international scientific publications resulted by Indonesian Partners, especially joint publications (co-authorship) Indonesian researchers and foreign researchers, is still very low. This study examines the research management undertaken by Indonesian partner institutions in international collaborative research and its positive impact on scientific publication performance. The research adopts a qualitative approach. Primary data were collected through structured in-depth interviews with 31 key informen selected using purposive method. Risk management analysis has been applied as theoretical framework to explain the implementation of research partnership carried out by Indonesian partner institutions in international research collaboration. The performance of scientific publications is more an achievement of strengthening management undertaken by Indonesian partner institutions formulated into mutually agreed clauses in collaborative research agreements with foreign institutions, rather than being the outcome of foreign research permit policy.